Analisis Faktor-Faktor Yang Mempengaruhi Keterlambatan Dalam Penyelesaian Laporan Audit (Studi Kasus Pada KAP XYZ) - Ali, Muhammad Fauzi; Surya, Firman; Zahara, Zahara (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2024)
This study aims to analyze what factors influence the delay in completing audit reports at KAP XYZ. This research uses a qualitative method with a descriptive design. Research data obtained through interviews. Based on the results of interviews with KAP XYZ auditors, conclusions can be drawn which include (1) Internal factors that cause delays in completing audit reports include lack of human resources, auditor overload, and auditor competence. Then, (2) External factors that cause delays in completing the audit report include delays in providing documents, unfriendly responses from clients, and data lost during delivery. The results of this study will help the auditor profession in an effort to improve the efficiency and effectiveness of the audit process so as to reduce or even avoid delays in completing audit reports at KAP XYZ.